Resin composition for friction material
A thermoplastic resin composition for friction materials, featuring a high Tg polyamide resin and specific inorganic fillers, addresses the challenge of maintaining stable friction and wear characteristics at high temperatures, facilitating mass production and reducing environmental impact.
Patent Information
- Application Number
- JP2021057605
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2041-03-30
AI Technical Summary
Friction materials used in small collaborative robots require stable friction and wear characteristics at high temperatures, but existing thermoplastic resin compositions exhibit unstable physical properties and increased wear at elevated temperatures.
A resin composition for friction materials is developed, comprising at least 70% by volume of a thermoplastic resin with a glass transition temperature (Tg) of 120° C. or more, specifically a polyamide resin with a dicarboxylic acid component mainly composed of terephthalic acid and a diamine component mainly composed of 1,10-decanediamine, combined with a first inorganic filler (glass fiber) and a second inorganic filler (layered silicates, inorganic whiskers, and sulfate salts) to ensure injection moldability and stable friction and wear characteristics.
The resin composition achieves stable and excellent friction and wear characteristics from room temperature to 150° C., enabling mass production by injection molding and reducing environmental impact through the use of biomass-derived raw materials.
Smart Images

Figure 0007662936000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a friction material, and more particularly to a resin composition for a friction material formed by injection molding. [Background technology]
[0002] Conventionally, friction materials based on thermosetting resins have been used in brakes for automobiles and brakes for servomotors mounted on the drive parts of each joint of a large industrial robot. For friction materials used for such purposes, high safety is required, so friction materials based on phenolic resin, which is a thermosetting resin having stable friction and wear characteristics under high load and high temperature environments, are used (Patent Documents 1 and 2). The resin composition used for such friction materials has poor melt fluidity due to the small amount of resin, and the filler with high Mohs hardness contained in the resin composition may damage the screw, cylinder, and nozzle inner surface of the injection molding machine, and the runner and gate parts of the mold, so a compression molding method is generally adopted.
[0003] In addition, the problem of global warming caused by an increase in the concentration of carbon dioxide in the atmosphere is becoming a worldwide issue, and various industrial fields are also developing technologies to reduce carbon dioxide emissions. In light of this background, an environmentally friendly friction material has been proposed in which phenolic resin is blended with lignocellulose fibers derived from plant biomass (Patent Document 2).
[0004] On the other hand, thermoplastic resins are widely used for sliding components, and in particular, super engineering plastics such as polyphenylene sulfide (PPS) and polyether ether ketone (PEEK) are widely used under harsh sliding conditions, such as high temperature environments. In recent years, polyamide 10T derived from plant biomass has been studied as a sliding material (Patent Documents 3 to 5). The glass transition point (hereinafter, Tg) of polyamide 10T is about 160° C., which is higher than that of PPS and PEEK. By blending fibrous reinforcing materials and sliding property improvers with polyamide 10T, low friction properties and wear resistance are imparted, and each has been proposed as a resin composition for sliding materials. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2018-131477 A [Patent Document 2] JP 2019-137705 A [Patent Document 3] Patent No. 5804313 [Patent Document 4] Patent No. 6249711 [Patent Document 5] JP 2018-169021 A Summary of the Invention [Problem to be solved by the invention]
[0006] Friction materials installed in large industrial robots are used in high-load applications and are required to have high friction properties, wear resistance, and the ability to handle emergency braking. During emergency braking, a large frictional force is applied, and the frictional heat causes the wear surface to become very hot, resulting in molten wear. For this reason, friction materials based on phenolic resin, a thermosetting resin, are used. Meanwhile, in recent years, in the field of industrial robots, there has been an increasing demand for small collaborative robots that can work directly with humans in various manufacturing processes without installing safety fences. Small collaborative robots capable of light work are expected to be used not only in the industrial field where large industrial robots have been introduced, but also in various service industries such as food, cosmetics, medical care, and nursing care, and in primary industries.
[0007] For the friction materials installed in these small collaborative robots that perform light work, emergency braking is not considered important, and heat resistance and high friction characteristics are not required as much as those of phenolic resin-based friction materials, but considering the future spread of these robots in various fields, friction materials will also need to be easy to mass-produce. From these perspectives, it is thought that the need for thermoplastic resin-based friction materials will increase.
[0008] In addition, Patent Document 2 states that an environmentally friendly friction material has been developed, but the content of plant biomass-derived lignocellulose fibers in the resin composition is very low, at 2 to 5 mass %. Currently, from the perspective of the SDGs (Sustainable Development Goals), there is a global demand for the development of products with a smaller environmental impact.
[0009] Typically, in the drive parts of the joints of collaborative robots and the like, various elements such as drive motors and electromagnetic coils are incorporated in a relatively small space, and considering the heat generated by these elements and the heat generated by friction of the friction material, the operating atmosphere of the friction material becomes as high as about 120°C. Therefore, the friction material that operates in these parts needs to have stable characteristics over a wide temperature range, from room temperature to high temperatures.
[0010] In general, compared with thermosetting resins, the physical properties of thermoplastic resins are more susceptible to change depending on temperature, and the degree of change is particularly large around Tg. However, when used as a friction material, a material with stable friction and wear characteristics in the operating atmosphere temperature range is suitable, so it is necessary to select a resin composition based on a thermoplastic resin that has a small temperature dependency of the friction coefficient and excellent wear resistance not only at room temperature but also at 120°C to 150°C.
[0011] Patent Documents 3 to 5 state that the friction coefficient can be reduced and excellent wear resistance can be obtained by blending a fibrous reinforcing material such as glass fiber or carbon fiber and a sliding property improver with a base resin of polyamide 10T. However, there is no description of the high friction, low wear properties, and stable friction and wear properties at high temperatures that are necessary for a friction material.
[0012] Therefore, an object of the present invention is to provide a resin composition for a friction material which has stable and excellent friction and wear properties in the range from room temperature to a temperature higher than about 120° C. and which can be injection molded. [Means for solving the problem]
[0013] The resin composition for friction materials of the present invention is characterized by containing 70% by volume or more of a thermoplastic resin containing at least a polyamide resin having a Tg of 120°C or more, a first inorganic filler having a Mohs hardness of 5 or more, and a second inorganic filler having a Mohs hardness of less than 5.
[0014] The polyamide resin is characterized in that it is mainly composed of a dicarboxylic acid component mainly composed of terephthalic acid and a diamine component mainly composed of 1,10-decanediamine.
[0015] The polyamide resin is characterized by containing the radioactive isotope carbon-14.
[0016] The first inorganic filler and the second inorganic filler are contained in a total amount of 20% by volume or more and 30% by volume or less.
[0017] The first inorganic filler is contained in an amount of 10% by volume or more and 20% by volume or less.
[0018] The first inorganic filler is characterized in that it is glass fiber.
[0019] The second inorganic filler is characterized in that it contains at least two types.
[0020] The second inorganic filler is contained in an amount of 10% by volume or more and 20% by volume or less.
[0021] The second inorganic filler is characterized in that it contains inorganic whiskers in an amount of 5 vol % to 10 vol % and a sulfate in an amount of 5 vol % to 10 vol %.
[0022] A friction material using the above friction material composition.
[0023] A servomotor equipped with a braking device using the aforementioned friction material.
[0024] The present invention relates to a collaborative robot equipped with the aforementioned servo motor.
[0025] The component compositions of the polyamide resin and inorganic filler contained in the friction material can be identified by analytical methods such as infrared spectroscopy, mass spectrometry, and characteristic X-ray analysis. Effect of the Invention
[0026] According to the present invention, it is possible to provide a resin composition for a friction material which has stable and excellent friction and wear properties in the range from room temperature to a temperature higher than about 120° C. and which can be injection molded. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] The friction material according to an embodiment of the present invention is characterized in that it contains 70% by volume or more of a thermoplastic resin containing at least a polyamide resin having a Tg of 120°C or more, a first inorganic filler having a Mohs hardness of 5 or more, and a second inorganic filler having a Mohs hardness of less than 5.
[0028] In this way, by using a resin composition that combines a polyamide resin with a Tg of 120°C or higher and a specific inorganic filler, it is possible to provide a friction material that can exhibit friction and wear characteristics that are suitable for, for example, collaborative robots.
[0029] Friction materials installed in large industrial robots are required to respond to sudden braking in emergency situations. When sudden braking occurs in an emergency, a very large frictional force acts on such friction materials, which become very hot due to the heat generated by this friction, causing melting and wear. For this reason, phenolic resin based on thermosetting resin is used as the main component, and various inorganic fillers are mixed and obtained by compression molding.
[0030] However, since it is predicted that the need for small collaborative robots capable of light work will rapidly increase in the future, it is thought that there will be an increased need for friction materials based on thermoplastic resins, which will not require the same heat resistance and high static friction characteristics as conventional friction materials based on thermosetting resins.
[0031] In addition, since thermosetting resin-based resin compositions are generally difficult to recycle, they are often disposed of as landfills, which is one of the causes of environmental problems, whereas thermoplastic resin-based resin compositions can be recycled, which can reduce the amount of waste.
[0032] In general, when a thermoplastic resin is placed in a high-temperature environment, particularly above its Tg, various physical properties change, causing problems such as an unstable and irregular fluctuation in the friction coefficient and an increase in the amount of wear, making it difficult to use the resin as a friction material resin composition.
[0033] However, as a result of investigations by the present inventors, it has become clear that by using a combination of a polyamide resin having a Tg of 120°C or higher and an inorganic filler having a predetermined Mohs hardness as the resin component, it is possible to perform injection molding suitable for mass production and to obtain a resin composition for friction materials in which fluctuations in the friction coefficient and increases in the amount of wear are suppressed in the temperature range from room temperature to 150°C.
[0034] Such a resin composition for friction materials can be obtained by injection molding a thermoplastic resin composition containing, for example, 70 vol% or more of a thermoplastic resin containing at least the polyamide resin, 10 vol% or more to 20 vol% or less of a first inorganic filler having a Mohs hardness of 5 or more, and 10 vol% or more to 20 vol% or less of a second inorganic filler having a Mohs hardness of less than 5. The polyamide resin has a Tg of 120°C or more, and by using the polyamide resin in a predetermined blending ratio, a thermoplastic resin-based resin composition for friction materials having stable and good friction and wear properties even at room temperature in a range higher than about 120°C can be obtained by injection molding.
[0035] The polyamide resin preferably has a Tg of 120°C or higher, more preferably 150°C or higher. This polyamide resin is particularly suitable as a friction material for collaborative robots because it can maintain its friction and wear properties at room temperature even at high operating ambient temperatures (about 120°C). The Tg of the polyamide resin can be measured using a differential scanning calorimeter (DSC). A measurement sample is prepared by quenching the polyamide resin from a heated and molten state to room temperature under an inert gas atmosphere, and the measurement sample is measured by DSC. The baseline shift temperature appearing in the obtained DSC curve is taken as the Tg. (In accordance with JIS K7121) In thermoplastic resins such as the polyamide resin, the molecular chains of the resin start to move at a temperature equal to or higher than the Tg, which is an indicator of the heat resistance temperature of a composition using the resin.
[0036] Examples of polyamide resins that have a Tg of more than 120° C. and can be injection molded include polyamide 4T, polyamide 6T, polyamide 9T, polyamide 10T, etc. Among these, polyamide 10T is preferred because it has a Tg of 150° C. or higher.
[0037] The polyamide resin used in the present invention is composed of a dicarboxylic acid component, and is obtained by polycondensation of the dicarboxylic acid and diamine constituting each component. The dicarboxylic acid component constituting the polyamide resin is mainly composed of terephthalic acid, which makes the polyamide resin excellent in heat resistance, high rigidity, etc. The diamine component constituting the polyamide resin is mainly composed of 1,10-decanediamine. Diamines mainly composed of 1,10-decanediamine are linear aliphatic diamines. Both terephthalic acid and 1,10-decanediamine have highly symmetric chemical structures, so by using them as the main components, a highly crystalline polyamide resin can be obtained.
[0038] In the polyamide resin used in the present invention, a biologically derived raw material may be used as the dicarboxylic acid component or diamine component. For example, 1,10-decanediamine, which is made from castor oil obtained from a non-edible plant called castor bean, can be used. By using a plant-based biomass-derived raw material, the actual amount of carbon dioxide emitted from the incineration of friction material can be reduced compared to when biomass-derived raw materials are not used. Here, whether or not a plant-based plastic is made from biomass-derived raw materials can be determined by checking whether the carbon constituting the resin is a radioisotope, 14 It can be distinguished by measuring the concentration of C. 14 Since the half-life of C is 5730 years, carbon derived from fossil resources that is thought to have been generated over 10 million years 14 This means that the resin does not contain any C. 14 If it contains C, it can be determined that the raw materials used are at least biomass-derived.
[0039] The blending ratio of the polyamide resin in the resin composition is preferably 70% by volume or more. More preferably, it is 70% by volume or more and 80% by volume or less. If it is less than 70% by volume, it is difficult to ensure the flowability in kneading extrusion and injection molding, and moldability is deteriorated. Also, if it is 70% by volume or more, it is possible to ensure the flowability in kneading extrusion and injection molding, but if it exceeds 80% by volume, the friction and wear properties at high temperatures are reduced.
[0040] Furthermore, if the blending ratio of the polyamide resin is reduced, the proportion of raw materials derived from biomass such as living organisms in the resin composition will be lower, and the effect of reducing the environmental load will be smaller. Incidentally, the Japan Bioplastics Association defines the biomass plastic degree as "the proportion (weight %) of the biomass-derived components in the biomass plastic composition contained in raw materials and products to the total weight," and certifies plastic products with a biomass plastic degree of 25.0 weight % or more as biomass plastics.
[0041] The first inorganic filler preferably has a Mohs hardness of 5 or more, and more preferably has a Mohs hardness of 5 or more and less than 7 in order to ensure better injection moldability. In order to achieve a high friction coefficient, a filler with a high Mohs hardness, such as alumina (Mohs hardness: 9) or zirconia (Mohs hardness: 7.5), may be added, but this is problematic in injection molding because it damages the screw and cylinder. Therefore, glass fiber (Mohs hardness: 6 to 7) and rock wool (Mohs hardness: 6) are more preferable. The Mohs hardness can be determined by whether or not the standard mineral is scratched when rubbed with 10 types of standard minerals with different hardness. A commercially available Mohs hardness tester can be used to measure the Mohs hardness.
[0042] The compounding ratio of the first inorganic filler having a Mohs hardness of 5 or more in the resin composition is preferably 10% by volume or more and 20% by volume or less. This allows the resin composition to have a desired friction coefficient as a friction material without impairing moldability. If it is less than 10% by volume, it becomes difficult to achieve a high friction coefficient. Also, if it exceeds 20% by volume, there is a risk of damage to the screw and cylinder during injection molding, and there is a risk of impairing moldability.
[0043] The second inorganic filler may be one having a Mohs hardness of less than 5, such as layered silicate, inorganic whisker, sulfate, carbonate, non-layered silicate (excluding inorganic whisker), minerals other than silicate (excluding inorganic whisker), calcium fluoride (excluding minerals), etc. It is preferable to include at least two of these. In this way, by including at least two inorganic fillers having a Mohs hardness of less than 5, injection moldability can be ensured even if the amount of resin is reduced compared to the case applied to normal injection molding, and the deterioration of friction and wear properties at high temperatures can be suppressed. In addition, in injection molding, the screw and cylinder are less likely to be damaged.
[0044] Examples of layered silicates include clay minerals such as kaolin, serpentine, talc, biotite, phlogopite, muscovite, and vermiculite.
[0045] Examples of inorganic whiskers include potassium titanate whiskers, zinc oxide whiskers, and magnesium sulfate whiskers.
[0046] Examples of sulfates include barium sulfate and calcium sulfate hydrate.
[0047] Examples of carbonates include calcium carbonate, magnesium carbonate, lithium carbonate, barium carbonate, potassium carbonate, and sodium carbonate.
[0048] Examples of non-layered silicates (excluding inorganic whiskers) include zeolites (boiling stones) and calcium silicates (excluding minerals).
[0049] Examples of minerals other than silicates (excluding inorganic whiskers) include dolomite, fluorite, calcite, and dolomite.
[0050] The blending ratio of the second inorganic filler having a Mohs hardness of less than 5 is preferably 10% by volume or more and 20% by volume or less for each of the at least two types of inorganic fillers in the resin composition. This ensures injection moldability and suppresses deterioration of friction and wear properties at high temperatures. In addition, the wear resistance and rigidity of the friction material can be improved.
[0051] In addition, the resin composition of the present invention may contain other components other than the above-mentioned polyamide resin, the specified inorganic fiber, and the inorganic filler, as long as the characteristics of the present invention are not impaired. Such components include those generally used in the relevant technical field, such as flame retardants, release agents, plasticizers, colorants, weather resistance agents, antioxidants, etc. In addition, when added, the total amount of these components in the resin composition is preferably 5% by volume or less.
[0052] The means for mixing the materials constituting the resin composition is not particularly limited, and two or more types may be mixed simultaneously using a general-purpose mixer such as a Henschel mixer, a ball mixer, or a ribbon blender.
[0053] The means for melt-kneading each material constituting the resin composition is not particularly limited, and can be melt-kneaded in a melt extruder such as a single-screw kneading extruder or a twin-screw kneading extruder to obtain pellets for molding. The filler may be added by using a side feed when melt-kneading in an extruder or the like. In that case, the kneading temperature is usually 300°C to 340°C, preferably 300°C to 320°C. The molding method can be extrusion molding, injection molding, or the like, and a uniform molten blend can be formed and then injection molding or extrusion molding can be performed. Among these, it is preferable to adopt injection molding because of its excellent productivity. During injection molding, the resin temperature is set to be equal to or higher than the melting point of the polyamide resin described above, and the mold temperature is maintained at 130°C to 150°C.
[0054] The friction material molded from the resin composition as described above has stable and excellent friction and wear properties both at room temperature and at temperatures above about 120° C., and can be mass-produced by injection molding, making it suitable for use in braking devices. The braking devices to which the friction material can be applied include, but are not limited to, brakes, clutches, and the like.
[0055] Braking devices equipped with the above-mentioned friction material are suitable for use in robots, various motors, actuators, unmanned guided vehicles, electric carts, electric shutters, and medical machines.
[0056] For example, a braking device equipped with the above-mentioned friction material is suitable for use in servo motors, particularly in small collaborative robots that perform light work. It is possible to provide a friction material that has good performance and is easy to mass-produce for collaborative robots, which are expected to become increasingly popular in the future. Furthermore, from the perspective of the SDGs, it is possible to provide products that have a low environmental impact.
[0057] Hereinafter, an embodiment of the friction material according to the present invention will be described based on examples.
[0058] (Examples 1 to 4) After dry mixing the components in the compounding ratio (volume %) shown in Table 1, the mixture was kneaded using a twin-screw kneading extruder (TEM-26SX, manufactured by Shibaura Machine Co., Ltd.), and while being taken out in the form of a strand from a die, it was passed through a water tank to be cooled and solidified, and then cut with a pelletizer to obtain a pellet-shaped resin composition. The pellets of the obtained resin composition were dried at 120°C for 16 hours in a hot air drying oven (PHH-201, manufactured by Espec Corporation), and various test pieces were produced by injection molding using an injection molding machine (PS60E5H, manufactured by Nissei Plastic Industrial Co., Ltd.). The molding temperatures were 310°C for the cylinder temperature and 130°C for the mold temperature.
[0059] (Comparative Examples 1 to 4) For Comparative Examples 1 to 3, test pieces were prepared by injection molding in the same manner as in Example 1, except that the compounding ratios shown in Table 1 were used. In Comparative Example 4, the kneading temperature was 290°C, and the molding temperatures during injection molding were 290°C for the cylinder temperature and 90°C for the mold temperature.
[0060] The components used in the examples and comparative examples are as follows. Polyamide 10T (PA10T): Unitika Ltd., Xecot, XN400 Polyamide 66 (PA66): Leona, 1300S, manufactured by Asahi Kasei Corporation Glass fiber: Central Glass Fiber Co., Ltd., chopped strand ECS03-615, Mohs hardness 6.5 Barium sulfate: Sakai Chemical Industry Co., Ltd., BA, elutriation grade, Mohs hardness 3 Potassium titanate whisker: Otsuka Chemical Co., Ltd., Tismo D, Mohs hardness 4
[0061] (evaluation) <Mold filling ability> For Examples 1 to 4 and Comparative Examples 1 to 4, the filling property of the test pieces into the mold during injection molding was evaluated by visually inspecting the appearance of the test pieces and cavities, which were injection molded products. The evaluation criteria were as follows. A completely filled product was evaluated as being usable as an injection molded product. The evaluation results are shown in Table 1. ○: Completely filled, ×: Filling impossible or not filled. Melt kneading extrusion is difficult.
[0062] <Friction and wear characteristics> Using cylindrical test pieces of φ5 mm×10 mm obtained as injection molded products that were completely filled in the examples and comparative examples, the static friction coefficient of each sample was measured with a pin-on-disk type friction and wear tester (Auto Pin Disk APD-101, manufactured by Starlite Industrial Co., Ltd.), and the specific wear rate was calculated. The test conditions were as follows. Surface pressure (load on sample): 0.1MPa Speed (set value): 0.05 m / s (static friction coefficient), 1.0 m / s (specific wear rate) Atmosphere: Air, room temperature, and 150℃ (static friction coefficient) In air, at room temperature, at 100℃ and 150℃ (specific wear rate) Lubrication: No lubrication Mating material: SPHC steel with surface roughness Ra ≒ 1.0 μm.
[0063] <<Static friction coefficient>> The bottom surface of the cylindrical test piece was placed in contact with the mating material, and the pin-on-disk type friction and wear tester was started. The peak value of the friction coefficient at the start was taken as the static friction coefficient. The speed (set value) at this time was 0.05 m / sec. This test was performed at room temperature and at 150°C. This tester has a heater built into the bottom of the mating material, and is structured so that the temperature of the mating material can be adjusted. When the temperature of the mating material needs to be adjusted, the heater is set to a specified temperature, the temperature of the mating material is adjusted, and the test is performed. The evaluation criteria are as follows. The measurement results are shown in Table 1. The friction coefficient reduction rate α in Table 1 is the value obtained by dividing the static friction coefficient at 150°C: μ (150°C) by the static friction coefficient at 25°C: μ (25°C). {α=μ(150℃) / μ(25℃)} 〇: 1.00≧α≧0.90, ×: α<0.90, α>1.00.
[0064] <<Specific wear rate>> The speed was set to 1.0 m / sec, and the change in the amount of wear over time was measured. From the wear progress curve showing the change in the amount of wear (height) over time obtained, the specific wear amount was calculated based on the following formula (1). The calculation results are shown in Table 1. The temperature of the mating material was regulated in the same manner as described above. The evaluation criteria are as follows. In this experiment, T' was set to 20 hours after the start of the test, and T was set to 10 hours after the start of the test. K = (H'-H) / {P·V·(T'-T)} (1) K: Specific wear amount [mm 3 / N·m H': wear amount (height) at test time T' [mm] H: Wear amount (height) at test time T [mm] P: Surface pressure [N / mm 2 ] V: Velocity [m / s] T': Test time in steady state [s] T: Test time in steady state [s] Steady state: The state in which the wear rate stabilizes after the test time. ○: 2.0×10 under all conditions at 25℃, 100℃, and 150℃ -5 [mm 3 / N m] or less, ×: 2.0×10 at either 25℃, 100℃, or 150℃ -5 [mm 3 / N m
[0065] The polyamide resin used this time was Polyamide 10T, which has a biomass plastic content of 56% by weight, calculated as a polymer. The Biomass Plastics Association certifies that plastic products with a biomass plastic content of 25.0% by weight or more are biomass plastics. Based on this, the environmental reduction effect was evaluated. The evaluation criteria are as follows: ◯: Biomass plastic content is 25.0% by weight or more, ×: Biomass plastic content is lower than 25.0% by weight.
[0066] The friction and wear characteristics were evaluated, and bending strength was evaluated for Examples 1 to 4 and Comparative Examples 1, 2, and 4. Although the friction and wear characteristics of Comparative Examples 1, 2, and 4 were inferior to those of the Examples, they were measured for reference.
[0067] <Bending strength> The bending strength of the test pieces obtained as injection molded products by completely filling the molded parts in the examples and comparative examples was measured using an autograph AG-Xplus manufactured by Shimadzu Corporation. The test piece shape and measurement conditions were in accordance with JIS K7171. The evaluation results are shown in Table 1.
[0068] [Table 1]
[0069] As shown in Table 1, in Examples 1 to 4, injection molding is possible, the ratio of the static friction coefficient at 150°C to the static friction coefficient at room temperature is 0.90 or more, and it is found that the friction and wear characteristics are stable and good both at room temperature and at a high temperature of 150°C. Furthermore, the biomass plastic content is 25.0% by weight or more, which contributes to reducing the environmental load more than conventional friction materials based on phenolic resin.
[0070] The friction material resin based on the thermoplastic resin of the present invention has stable and excellent friction and wear characteristics both at room temperature and in the range of temperatures above about 120°C, and can be mass-produced by injection molding, so it can be used in braking devices installed on robots, etc.
Claims
1. A resin composition for a friction material, comprising: The friction material resin composition contains 70% by volume or more of a thermoplastic resin consisting of only a polyamide resin having a glass transition point of 120° C. or more selected from polyamide 4T, polyamide 6T, polyamide 9T, and polyamide 10T, a first inorganic filler having a Mohs hardness of 5 or more, and a second inorganic filler having a Mohs hardness of less than 5, The friction material resin composition is characterized in that the friction coefficient reduction rate α (μ(150°C) / μ(25°C)), which is the value obtained by dividing the static friction coefficient μ(150°C) at 150°C by the static friction coefficient μ(25°C) at 25°C, is 0.90 or more and 1.00 or less.
2. 2. The resin composition for friction materials according to claim 1, wherein the polyamide resin is polyamide 10T.
3. 3. The resin composition for friction materials according to claim 1, wherein the polyamide resin contains carbon-14, which is a radioactive isotope.
4. 4. The resin composition for friction materials according to claim 1, wherein the first inorganic filler and the second inorganic filler are contained in a total amount of 20% by volume or more and 30% by volume or less.
5. 5. The resin composition for friction materials according to claim 1, wherein the first inorganic filler is contained in an amount of 10% by volume or more and 20% by volume or less.
6. 6. The resin composition for friction materials according to claim 1, wherein the first inorganic filler is a glass fiber.
7. The resin composition for friction materials according to any one of claims 1 to 6, wherein the second inorganic filler comprises at least two types of fillers.
8. 8. The resin composition for friction materials according to claim 1, wherein the second inorganic filler is contained in an amount of 10% by volume or more and 20% by volume or less.
9. The resin composition for friction materials according to any one of claims 1 to 8, characterized in that the second inorganic filler contains 5 vol% or more and 10 vol% or less of inorganic whiskers and 5 vol% or more and 10 vol% or less of sulfates.
10. A friction material using the friction material resin composition according to any one of claims 1 to 9.
11. A servomotor equipped with a braking device using the friction material according to claim 10.
12. A robot comprising the servo motor according to claim 11.
Citation Information
Patent Citations
JP131477A
JP137705A
JP169021A
Manufacture of electrode for electrospark machining and electrode therefor
JP1983004313A
Antenna system
JP1987049711A